A new mechanism for size separation of particles immersed in a fluid. (2017) - Orland, Ro'ee Z.; Katoshevski, David
Work presented deals with a new mechanism for particle size-separation based on differential grouping induced by a controlled oscillating flow field. This separation by size may be used for coagulation of like-sized particles. Flow oscillations are induced by a pulsating sphere. The dynamics of particles immersed in such a flow field and their trajectories are analysed mathematically based on perturbation analysis. It is shown that in proximity to the sphere, particle trajectories display strong dependence on particle size (through particle Stokes number), far more so than on initial position. Grouping behaviour is observed under specific operating conditions, and this suggests feasibility of applications in filtration systems, as well as for size-based separation.